Seroprevalence of antibodies against diphtheria, tetanus, and pertussis among healthy Thai adolescents - Pimpika Hanvatananukul; Chanidapa Prasarakee; Saowalak Sarachai; Linda Aurpibul; Kamolrawee Sintupat; Ratchaneekorn Khampan; Jutamad Saheng; Tavitiya Sudjaritruk (International Journal of Infectious Diseases, 2020)
Objective: To determine the seroprevalence of antibodies against of diphtheria, tetanus, and pertussis among Thai adolescents. Methods: A cross-sectional study was conducted among Thai adolescents aged 11–20 years who had completed five doses of diphtheria, tetanus, and pertussis (DTP)-containing vaccine during childhood, either diphtheria toxoid, tetanus toxoid, whole-cell pertussis (DTwP) or diphtheria toxoid, tetanus toxoid, acellular pertussis (DTaP) vaccine. Protective antibodies against diphtheria, tetanus, and pertussis were defined as anti-diphtheria toxoid IgG ≥0.1 IU/ml, anti-tetanus toxoid IgG ≥0.1 IU/ml, and anti-Bordetella pertussis toxin IgG ≥5 IU/ml, respectively. Results: Of 220 adolescents (median age 16 years), 45% had received a tetanus toxoid, reduced diphtheria toxoid (Td) booster vaccine during adolescence, and none (0%) had received a tetanus toxoid, reduced diphtheria toxoid, acellular pertussis (Tdap) booster vaccine. Overall, 50%, 99%, and 57% of adolescents demonstrated protective antibodies against diphtheria, tetanus, and pertussis, respectively. The geometric mean concentrations (GMCs) of antibodies against diphtheria (p = 0.06) and tetanus (p < 0.001) were higher among adolescents who had received Td vaccine. Nevertheless, the antibody levels against both diseases waned over time, regardless of Td booster vaccination. Likewise, pertussis antibody levels gradually declined after the fifth childhood dose of DTwP/DTaP vaccine. Conclusions: Approximately half of these healthy Thai adolescents had not maintained protective antibodies against diphtheria and pertussis. A booster vaccination with diphtheria toxoid and/or acellular pertussis-containing vaccines is a crucial strategy to prevent such diseases in this population.